Place of death and healthcare utilisation at the end of life among individuals with mental and behavioural disorders as underlying cause of death: population-level multiple-register study - Maja Magdalena Olsson; Christopher Holmberg; Cecilia Larsdotter; Stina Nyblom; Joakim Öhlén (BJPsych Open)
Background Understanding the place of death for individuals with mental and behavioural disorders (MBDs) is essential for identifying disparities in healthcare access and outcomes, as well as addressing broader health inequities within this population.